1995
DOI: 10.1159/000179082
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes Associated with Strangulation Obstruction in Cats

Abstract: While changes in blood flow associated with simple intestinal obstruction have been studied extensively, little is known about blood flow changes associated with strangulation obstruction. Closed loop strangulation was produced in anesthetized cats by means of a baby pressure gasket. Intestinal blood flow was measured by transit time flowmetry. Blood pressure was measured in a carotid artery and in veins of a closed loop of small intestine. The gasket pressure was increased stepwise in 10 mm Hg increments afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…We have previously provided evidence that strangulation obstruction in cats is associated with increased venous pressure and increased vascular resistance in the strangulated loop [1], which is in good agreement with observations made by Selkurt and Johnson [2], who showed that the vascular resistance in the small intestine of dogs increased when the venous pressure was increased from 0 to 22 mm Hg. Evidence has also been provided that resistance vessels as well as precapillary sphincters constrict in response to increased venous pressure in the small intestine [3,4], and Morishita et al [5] found that increased portal vein pressure resulted in elevated plasma concentration of endothelin.…”
Section: Introductionsupporting
confidence: 91%
“…We have previously provided evidence that strangulation obstruction in cats is associated with increased venous pressure and increased vascular resistance in the strangulated loop [1], which is in good agreement with observations made by Selkurt and Johnson [2], who showed that the vascular resistance in the small intestine of dogs increased when the venous pressure was increased from 0 to 22 mm Hg. Evidence has also been provided that resistance vessels as well as precapillary sphincters constrict in response to increased venous pressure in the small intestine [3,4], and Morishita et al [5] found that increased portal vein pressure resulted in elevated plasma concentration of endothelin.…”
Section: Introductionsupporting
confidence: 91%